Methylation in hepatocellular carcinoma - Santella, Regina M. (Iatreia, 2007)
The development of HCC is a complex, multistep, multistage process. The molecular pathogenesis of HCC appears to involve multiple genetic aberrations in the molecular control of hepatocyte proliferation, differentiation and death and the maintenance of genomic integrity. This process is influenced by the cumulative activation and inactivation of oncogenes, tumor suppressor genes and other genes. p53, a tumor suppressor gene, is the most frequently mutated gene in human cancers. There is also a striking sequence specific binding and induction of mutations by AFB1 at codon 249 of p53 in HCC. Epigenetic alterations are also involved in cancer development and progression. Methylation of promoter CpG islands is associated with inhibition of transcriptional initiation and permanent silencing of downstream genes. It is now known that most important tumor suppressor genes are inactivated, not only by mutations and deletions but also by promoter methylation. Several studies indicated that p16, p15, RASSF1A, MGMT, and GSTP1 promoter hypermethylation are prevalent in HCC. In addition, geographic variation in the methylation status of tumor DNA indicates that environmental factors may influence the frequent and concordant degree of hypermethylation in multiple genes in HCC and that epigeneticenvironmental interactions may be involved in hepatocarcinogenesis. We have found significant relationships between promoter methylation and AFB1-DNA adducts confirming the impact of environmental exposures on gene methylation. DNA isolated from serum or plasma of cancer patients frequently contains the same genetic and epigenetic aberrations as DNA isolated from an individual's tumor. The process by which tumor DNA is released into circulating blood is unclear but may result from accelerated necrosis, apoptosis or other processes. p53 mutation and p16 promoter hypermethylation have been detected in paired tumor and plasma of HCC cases. More recently, we investigated promoter hypermethylation in DNA isolated from the serum of HCC patients who provided repeated blood samples prior to diagnosis and controls enrolled in a cancer screen program in Taiwan. Among cases, aberrant methylation was found in serum DNA one to nine years before clinical HCC diagnosis. RASSF1A had the highest frequency of hypermethylation with 70% of cases having at least one positive sample compared to 44% for p16 and 22% for p15. For the controls, promoter hypermethylation was found in 6 and 4% of subjects for RASSF1A and p16, respectively; none had methylation of p15. An ROC curve that included clinical risk factors (age, HBsAg status, anti-HCV status, smoking, alcohol status) and hypermethylation biomarkers gave an overall predictive accuracy of 89% with sensitivity and specificity 84% and 94%, respectively. The analysis of epigenetic changes on RASSF1A, p16 and p15 tumor suppressor genes in serum DNA may be a valuable biomarkers for early detection in populations at high risk of HCC. In addition, the area of global hypomethylation remains largely unexplored in HCC.